The 2015 Illapel earthquake, central Chile: A type case for a characteristic earthquake?. Issue 2 (19th January 2016) - Tilmann, F.; Zhang, Y.; Moreno, M.; Saul, J.; Eckelmann, F.; Palo, M.; Deng, Z.; Babeyko, A.; Chen, K.; Baez, J. C.; Schurr, B.; Wang, R.; et al.
Abstract: On 16 September 2015, the M W = 8.2 Illapel megathrust earthquake ruptured the Central Chilean margin. Combining inversions of displacement measurements and seismic waveforms with high frequency (HF) teleseismic backprojection, we derive a comprehensive description of the rupture, which also predicts deep ocean tsunami wave heights. We further determine moment tensors and obtain accurate depth estimates for the aftershock sequence. The earthquake nucleated near the coast but then propagated to the north and updip, attaining a peak slip of 5–6 m. In contrast, HF seismic radiation is mostly emitted downdip of the region of intense slip and arrests earlier than the long period rupture, indicating smooth slip along the shallow plate interface in the final phase. A superficially similar earthquake in 1943 with a similar aftershock zone had a much shorter source time function, which matches the duration of HF seismic radiation in the recent event, indicating that the 1943 event lacked the shallow slip. Key Points: We determine a comprehensive rupture model for the 2015 Illapel earthquake Divergence between finite fault and backprojection source time functions indicates shallow slip The 1943 Illapel earthquake rupture was probably similar in the deeper parts but lacks shallow slip